KEPEMIMPINAN TRANSFORMATIF KEPALA MADRASAH DALAM MENGEMBANGKAN BUDAYA SUPERVISI KOLABORATIF DI MTS MINHAJUHAQ KABUPATEN PURWAKARTA - Afif, Lutfi Nur (UNISAN JURNAL, 2025)
This study aims to describe how the transformative leadership of the madrasah principal contributes to developing a collaborative supervision culture at MTs Minhajuhaq, Purwakarta Regency. The background of this study lies in the fact that supervisory practices in many schools remain administrative and centralized, giving teachers limited space for discussion, reflection, and collaboration in improving their pedagogical competence. Transformative leadership is considered relevant because it emphasizes cultural change through role modeling, motivation, intellectual stimulation, and individualized consideration. This research employed a qualitative approach with a case study design. Data were collected through in-depth interviews, classroom observations, reflective discussions, and documentation analysis, then analyzed using the Miles and Huberman interactive model. The findings reveal that the principal applies all four dimensions of transformative leadership consistently within the supervision process. The principal establishes a clear and humanistic vision of collaborative supervision, provides inspiration through exemplary behavior, and encourages teachers to experiment with innovative learning strategies. Supervision is conducted through friendly classroom observations, constructive two-way feedback, and reflective group forums that enable teachers to share experiences and best practices. The collaborative supervision culture develops as teachers’ motivation increases, reflective abilities grow, and trust strengthens between the principal and teachers. This transformation positively impacts teachers’ pedagogical competence, particularly in lesson planning, teaching methodology, and classroom management. The study concludes that transformative leadership is an effective and relevant approach for building a collaborative supervision culture in madrasahs. This approach not only strengthens teachers’ professionalism but also promotes a supportive and participatory work climate. These findings offer valuable insights for other Islamic educational institutions aiming to develop supervision practices focused on continuous professional development.